DAMPAK BOIKOT PERUSAHAAN STARBUCKS PADA PENJUALAN PRODUKNYA DI INDONESIA - Mubarok, Ahmad Ghazy Al; Fauzan, Muhammad Fitrah; Rosadi, Fatur Septian; Aditya, Rizky Aulia (Cahaya Ilmu Bangsa, 2025)
Starbucks Company is a giant coffee company in the world, famous for its delicious products, quality, price, uniqueness, and distinctiveness, but it must disappear due to involvement in issues in providing support to Israel for the Israeli-Palestinian conflict. Making Starbucks Company affected by the boycott movement on its image, the impact on its declining sales, and also the steps that must be taken by Starbucks to straighten out the issue. This study was conducted using a literature study methodology with the aim of obtaining collective information on the formulation of the problem and producing a complete study on the results of the formulation of the problem. The results of this study indicate that the consequences received by Starbucks are that the image of its products becomes bad and is subject to vandalism, the impact on its sales decreases, then the steps taken after being affected by the boycott movement are to deny the existing issues by the Starbucks CEO directly and in several existing outlets.